Scope and Challenges of Internet of Things (IoT) in Kashmir (International Journal of Engineering and Computer Science, 2018)
Internet of things is a fast growing technology that shall be shaping overall living standards of human beings all over the world. It, however like all other technological advancements, is dependent on certain factors. This paper tries to evaluate the scope, chances of growth and challenges that can hinder its survival in Kashmir.